Callerya Atropurpurea shells derived nitrogen doped carbon quantum dots of electrodes for symmetrical and asymmetrical supercapacitors - Abdulrahman Oyekanmi Adeleke; Mohd Arif Dar; Temitope T. Dele-Afolabi; R. C. Omar; Rasykin Roslan; Akil Ahmad; Ebrahim Mahmoudi; Chua Siew Fen; Ali Orozi Sougui; Mohammed B. Alshammari (Scientific Reports)
Abstract Callerya Atropurpurea shells were utilized as activated carbon precursors in a one-stage activation process at 700 °C using H2SO4, NaOH and KOH as activating agents. Herein, carbon quantum dots (CQDs) were produced via self-doping using urea as a nitrogen source. The structural, functional, and morphological properties of the doped active materials were examined using X-ray diffraction, Fourier transform infrared spectroscopy, and Raman spectroscopy. The elemental composition was conducted using energy-dispersive X-ray spectroscopy, and surface sensitivity was determined using X-ray photoelectron spectroscopy techniques. The surface properties showed that the nitrogen-doped CQDs produced good crystallinity with an abundance of nitrogen heteroatoms attached to the surface, facilitating the conductivity of the devices. The electrodes of NCQDs-1, NCQDs-2 and NCQDs-3 were prepared and used for the fabrication of asymmetric and symmetric supercapacitor electrodes. The NCQDs-3 electrode used in the asymmetric and symmetrical devices showed a higher specific capacitance of 22 F/g at a current density of 0.5 A/g. Also, the NCQDs-3 electrode achieved the highest coulombic efficiency of 98% and a capacitive retention of 99% even after 1000 GCD cycles.